2010
DOI: 10.1007/s00605-010-0270-4
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbolicity of the trace map for a strongly coupled quasiperiodic Schrödinger operator

Abstract: We consider the trace map associated with the silver ratio Schrödinger operator as a diffeomorphism on the invariant surface associated with a given coupling constant and prove that the non-wandering set of this map is hyperbolic if the coupling is sufficiently large. As a consequence, for this values of the coupling constant, the local and global Hausdorff dimension and the local and global box counting dimension of the spectrum of this operator all coincide and are smooth functions of the coupling constant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…This makes the silver type number case an interesting object to study. We note that in [16], the trace map related to silver number has been studied. They showed that the non-wandering set of this map is hyperbolic if the coupling is sufficiently large.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This makes the silver type number case an interesting object to study. We note that in [16], the trace map related to silver number has been studied. They showed that the non-wandering set of this map is hyperbolic if the coupling is sufficiently large.…”
Section: Introductionmentioning
confidence: 99%
“…Acknowledgements. The author would like to thank professor Anton Gorodetski for pointing out the references [16,23,32,34], which are closely related to this paper. He also thanks professor Jean Bellissard for pointing out that the results actually hold for more general frequencies, namely, frequencies of eventually constant type and encouraging me to write down this new version, which greatly improves the previous version of the paper.…”
mentioning
confidence: 97%
“…We can now apply Theorem 2.1 with G : Ω → GL(2, R) given by G(ω) = T ω,1 , in which case T (N ) ω = G(T N −1 ω)G(T N −2 ω) · · · G(ω) (recall that T : Ω → Ω is the left shift). That G is continuous is obvious, since G depends only on the first element of the sequence ω; also every entry of G(ω) is strictly positive, as is evident from (22). Now applying Theorem 2.1 on both sides of the inequality in (24), we see that…”
Section: 3mentioning
confidence: 82%
“…That G is continuous is obvious, since G depends only on the first element of the sequence ω; also every entry of G(ω) is strictly positive, as is evident from (22). Now applying Theorem 2.1 on both sides of the inequality in (24), we see that…”
Section: 3mentioning
confidence: 82%
“…Sinai on thermodynamic formalism]). The method of trace maps has led, for example, to fundamental results in spectral theory of discrete Schrödinger operators and Ising models on one-dimensional quasi-periodic lattices (for Schrödinger operators: [5,12,14,15,17,18,20,23,48,60,71], for Ising models: [6,7,13,24,33,74,76,84], and references therein).…”
Section: Introductionmentioning
confidence: 99%